Improving Health Literacy on Anemia Prevention Among Female Adolescents Through School-Based Interventions: Peningkatan Pengetahuan Remaja Putri Tentang Pencegahan Anemia Melalui Promosi Kesehatan Berbasis Sekolah - Putri Sulistian, Salwah; Pratiwi Putri, Bella; Galih Rahmadana, Adly; Ahmad, Islamudin (B-Creta Publisher, 2025)
Background: Adolescent girls are particularly vulnerable to iron-deficiency anemia due to increased nutritional demands during growth, regular iron loss through menstruation, and inadequate dietary intake. This condition negatively affects concentration, physical development, and overall productivity. Objective: This community engagement initiative aimed to improve adolescents’ knowledge and awareness of anemia prevention through school-based health education and iron supplementation. Methods: A school-based health promotion activity was conducted on June 17, 2025, at SMPN 11 Samarinda, involving 15 participants. The intervention included a pre-test, interactive educational session, post-test, and distribution of iron supplement tablets. Evaluation was carried out using the Wilcoxon test and participatory observation. Results: The intervention led to a statistically significant improvement in participants’ knowledge of anemia prevention (Z = -3.457; p < 0.001), with median scores increasing from 7 to 9 and interquartile range narrowing from 2 to 1, indicating more consistent understanding. Conclusion: This school-based educational initiative effectively enhanced health literacy among adolescent girls regarding anemia prevention and supports broader promotive-preventive health strategies aligned with national and global health agendas.